Smoking among adolescents in Northern Greece: a large cross-sectional study about risk and preventive factors - Spyratos Dionisios G; Pelagidou Despoina T; Chloros Diamantis; Haidich Anna-Bettina; Karetsi Eleni; Koubaniou Christina; Konstantopoulos Stavros; Gourgoulianis Konstantinos; Sichletidis Lazaros T (BMC, 2012)
Abstract Background The aim of the present study was to investigate epidemiological data about cigarette smoking in relation with risk and preventive factors among Greek adolescents. Methods We randomly selected 10% of the whole number of schools in Northern Greece (133 schools, 18,904 participants were included). Two anonymous questionnaires (smoker's and non-smoker's) were both distributed to all students so they selected and filled in only one. A parental signed informed consent was obtained using an informative leaflet about adolescent smoking. Results The main findings of the study were: a) 14.2% of the adolescents (mean age+/−SD: 15.3+/−1.7 years) reported regular smoking (24.1% in the age group 16-18 years), b) 84.2% of the current smokers reported daily use, c) students who live in urban and semirural areas smoke more frequently than those in rural areas, d) students in technically oriented schools smoke twice as frequent compared to those in general education, e) risk factors for smoking: male gender, low educational level of parents, friends who smoke (OR: 10.01, 95%CI: 8.53-11.74, p<0.001), frequent visits to internet cafes (OR:1.53, 95%CI: 1.35-1.74, p<0.001), parents, siblings (OR:2.24, 95%CI: 1.99-2.51, p<0.001) and favorite artist (OR:1.18, 95%CI: 1.04-1.33, p=0.009) who smoke, f) protective factors against smoking: participation in sports (OR:0.59, 95%CI: 0.53-0.67, p<0.001), watching television (OR:0.74, 95%CI 0.66-0.84, p<0.001) and influence by health warning messages on cigarette packets (OR:0.42, 95%CI: 0.37, 0.48, p<0.001). Conclusions Even though prevalence of cigarette smoking is not too high among Greek adolescents, frequency of everyday cigarette use is alarming. We identified many social and lifestyle risk and preventive factors that should be incorporated in a national smoking prevention program among Greek adolescents.